Methods of forming compositions and compositions formed therefrom

By forming a solvent mixture containing polymer and solvent in the fill composite material and precipitating it with non-solvent, the problem of difficult to achieve high filler content and uniform distribution in the prior art is solved, and high surface exposure and performance improvement are achieved.

CN119463278APending Publication Date: 2025-02-18TEEBS R&D LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411678349.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-05-07
Filing Date
2019-05-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art has difficulty achieving high filler content, uniform distribution and high surface exposure in fill composites, resulting in performance degradation in many applications, such as the ion flow capability and electron flowability of battery electrodes.

Method used

By forming a solvent mixture containing a polymer and a solvent and precipitating it with a non-solvent, a composition containing a filler in a fibrillated polymer matrix is ​​formed. This method allows for high filler content and uniform distribution and maintains the structural integrity of the composition by polymer fibrillation.

Benefits of technology

High filler content and uniform distribution are achieved, and the exposure of the filler surface is improved, thereby improving the ion flow and electron flow performance of the battery electrodes, reducing the cost and functional risks of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463278A_ABST
    Figure CN119463278A_ABST
Patent Text Reader

Abstract

The present application relates to methods of forming compositions and compositions formed therefrom. In one aspect, a method of making a composition comprises: forming a solvent mixture comprising a polymer and a solvent; precipitating the solvent mixture with a non-solvent to form a filler-containing composition in the fibrillated polymer matrix wherein the composition is in the form of particles and at least one of the solvent and the non-solvent comprises a filler; and separating the composition from the solvent and the non-solvent to isolate the composition. In another aspect, a porous material in which filler particles are mechanically bonded together by a polymer, and in which the polymer is present in filaments that adhere to and join the filler particles across interstitial spaces between the filler particles. In another aspect, a porous material precipitated from a polymer solution produced by phase inversion, in which a majority of the liquid can be mechanically removed.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a Chinese patent application filed on May 7, 2019, with application number "201980030953.3" and invention name "Method of forming a composition and composition formed thereby". The original application is the Chinese national phase application of international application PCT / US2019 / 031065. Technical Field

[0002] The present disclosure generally relates to a method of forming a composition and compositions formed therefrom. Background Art

[0003] Applications of filled polymeric materials, such as battery electrodes, process equipment components, chemical detectors, sensors, filtration systems, etc., can benefit from direct, intimate and complete surface contact between the medium being treated, reacted, tested or processed and the filler used to achieve the process or conversion operation. At the same time, filled composite materials used in many of these different industries and operations must firmly attach solid particles or powders to a binder, usually a polymer material, while still allowing high surface exposure of the filler to achieve a high degree of interaction between the filler particles and the external fluid or medium. However, achieving this balance of bonding the filler particles together while maintaining high surface exposure with sufficient self-supporting structural integrity is difficult.

[0004] Typical filled composites have been prepared by a variety of processes including solution or slurry casting, sintering, extrusion, calendaring, compression molding, etc. However, these methods do not distinguish the location of the filler from the binder to a large extent because the filler material tends to aggregate before or during forming, resulting in difficulty in accessing the filler surface. In addition, these processes generally produce filler materials with a thin surface layer of binder that effectively encapsulates the filler, thereby limiting access to the encapsulated filler material. The end result is that filled composites prepared using these processes may have limited access to the surface of the filler material, resulting in reduced performance in many applications.

[0005] Battery electrodes, for example, contain filler particles (commonly referred to as active materials) that contact an electrolyte medium to conduct ions. The use of conventional processes to form active layers for electrodes may result in reduced surface exposure of the active material, which may limit the flow of ions into and out of each particle due to reduced accessibility of the electrolyte to the active material. In addition, the reduction in surface exposure of the active material due to the presence of a binder on the surface of the active material may result in an increase in the resistance of the composite material, thereby greatly reducing the flow of electrons through or around the deposited binder, resulting in poor battery electrodes. The final effect is that a battery having an electrode in which the level of exposed surface area of ​​such an active material is reduced may have lower rate performance (reduced power), which in turn may effectively result in a lower specific capacity (lower energy density).

[0006] Post-processing operations that have been used to compress active layers in electrodes to provide tighter packing and contact between conductive filler particles may also exacerbate these problems associated with poor surface exposure of active materials. For example, compression of filled composite active layers prepared using conventional processes, where the filler surface is not well exposed in or on the polymer film to begin with, may cause a further and significant reduction in the accessible surface area of ​​the filler surface due to a reduction in the interstitial volume or porosity between the filler particles. The reduction in accessible surface area occurs because the reduction in interstitial volume or porosity may reduce the accessibility of the filler material in the composite material of the electrolyte medium and the electrode. Ultimately, compression of the active layer may exacerbate the already limited accessibility of the electrolyte medium to the active material due to the collapse of the pores of the composite material and the reduction in the number of channels for ion flow, each of which may hinder battery performance.

[0007] Additional disadvantages of using conventional processes to make filled composites may include problems associated with solvent casting and problems associated with drying processes. These problems may include low coating thickness, slow drying rates of solvent or diluent carrier media, and the need to recover or incinerate the solvent, each of which may impose a heavy manufacturing cost burden. In addition, these processes may present a risk of reduced functionality of the filled composite in the final product because a binder-rich, filler-poor layer may form within the filled composite near the carrier substrate.

[0008] Therefore, it is desirable to have a process for forming a composition that can achieve one or more of the following: high filler content, uniform filler distribution, uniform porosity, or low surface coverage of the binder on the filler to allow better access to the surface area of ​​the filler material. It is also desirable if the process can allow easy, rapid, direct or low-cost production of a uniform, optionally highly filled composition with a controlled format containing a desired degree of void content / porosity (which would otherwise be insignificant) final film macrostructure. Summary of the invention

[0009] Disclosed herein is a method of forming a composition and a composition formed thereby.

[0010] In one aspect, a method of preparing a composition comprises: forming a solvent mixture comprising a polymer and a solvent; precipitating the solvent mixture with a non-solvent to form a composition comprising a filler in a fibrillated polymer matrix, wherein the composition is in the form of particles and at least one of the solvent and the non-solvent comprises the filler; and separating the composition relative to the solvent and the non-solvent to isolate the composition.

[0011] In another aspect, a porous material made by a phase inversion process, wherein after removal of solvent and non-solvent, filler particles are mechanically bound together by a polymer, and wherein the polymer exists as filaments that adhere to and connect the filler particles through interstitial spaces between the filler particles; and wherein individual filler particles have bonded filament connections to one or more other particles.

[0012] In another aspect, a precipitated polymer solution produced by phase inversion wherein a majority of the liquid, typically 90% or more, including solvent and non-solvent, can be mechanically removed such as by at least one of filtration, settling, decantation, centrifugation, spraying, or cake compaction.

[0013] The above described and other features are exemplified by the following drawings, detailed description and appended claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] The following drawings are exemplary aspects and are provided to illustrate the present disclosure. The drawings are illustrative examples and are not intended to limit devices made according to the present disclosure to the materials, conditions or process parameters set forth herein.

[0015] Figure 1 is a photographic image of the carbon-PVDF layer of Example 1;

[0016] Figure 2 is a scanning electron microscope image of the carbon-PVDF layer of Example 1;

[0017] Figure 3A is a scanning electron microscope image of the carbon-PVDF layer of Example 1 (cross-section × 1000 view);

[0018] Figure 3B is a scanning electron microscope image of the carbon-PVDF layer of Example 1 (cross-section × 2500 view);

[0019] Figure 4 is a scanning electron microscope image of an unfilled polymer film prepared according to U.S. Patent No. 8,147,732 of Example 2;

[0020] Figure 5 is a scanning electron microscope image of an unfilled polymer film prepared according to U.S. Patent No. 8,147,732 of Example 2;

[0021] Fig.6A1 is a top view of the phase inversion method of Example 3;

[0022] Fig.6A2 is a side view of the phase inversion method of Example 3;

[0023] Fig.6B1 is a top view of the comparative phase inversion method of Example 3;

[0024] Figure 6B2 is a side view of the comparative phase inversion method of Example 3;

[0025] Fig. 7A is a scanning electron microscope image of the PVDF of Example 4 after the salt is removed;

[0026] Figure 7B Is from Fig. 7A Graphical analysis of the levels of periodic elements in the composition; and

[0027] Figure 7C Is from Fig. 7A Diagram of the levels of the periodic elements in the composition. DETAILED DESCRIPTION

[0028] A method for preparing a composition has been developed. The method includes: forming a solvent mixture comprising a polymer matrix and a solvent; combining the solvent mixture with a non-solvent to form a precipitate of a composition comprising a fibrillated polymer; and separating the precipitate relative to the solvent and the non-solvent. At least one of the solvent mixture or the non-solvent comprises a filler. A layer can be formed from a composition comprising multiple structures. If desired, the composition can be densified by applying a physical force such as by calendaring. The composition can include: 0 weight percent (wt%) to 95 weight percent of filler, or greater than or equal to 85 weight percent of filler, or 75 weight percent to 99 weight percent of filler; and 5 weight percent to 100 weight percent, or 1 weight percent to 15 weight percent, or 1 weight percent to 25 weight percent of a fibrillated polymer matrix, wherein the weight is based on the total weight of the composition. As used herein, the amount based on the composition is determined based on the solid and in the absence of any solvent or non-solvent. Without being bound by theory, it is believed that the present method produces a composition with a different morphology, including a higher proportion of exposed surface area of ​​filler or multi-scale porosity, compared to compositions prepared by different methods. It is also believed that the presence of the polymer matrix fibrils may act as a matrix stabilizer, exerting various stresses on the filler particles to maintain the structural integrity of the composition at least during formation of the composition, thereby enabling it to become a self-supporting layer.

[0029] The present method can produce a composition having a filler content of greater than or equal to 90 volume percent (vol%) based on the total volume of the composition, wherein the filler particles are attached to the polymer or embedded within the composition in a manner that provides a very high level of exposed surface area of ​​the filler particles. Incorporating large amounts of fillers can be beneficial in reducing the overall cost of the article by minimizing the polymer content or providing additional functional properties to the product. These properties can be multiple and, if not specifically stated, can include at least one of catalytic / enzymatic action, filtering / binding properties to other molecules, direct chemical reaction, or biological purification.

[0030] The method can produce the incorporation of a large amount of filler in the form of micron, submicron or smaller sized particles or powders, arranged in large quantities on the surface of an interconnected, porous or solid polymer matrix. The high degree of exposure of the filler material surface can be beneficial for the use of such materials in applications such as electrodes for battery applications and for other electrochemical applications, where greater surface exposure of the filler improves product performance.

[0031] The method may include utilizing a soluble filler that is at least partially soluble in at least one of a solvent, a non-solvent, or a third solvent different from the solvent and the non-solvent. The method may include dissolving the soluble filler during or after forming the composition to produce a composition that does not contain the soluble filler.

[0032] In one aspect, the soluble filler is compatible with the polymer such that the soluble filler is present in (dissolved in) the composition after phase inversion. The soluble filler is then dissolved from the composition to provide additional porosity. The filler may be completely removed from the composition or partially removed to provide a desired degree of additional porosity.

[0033] Post-processing techniques involving compression or effective densification of the above-mentioned filled compositions into a larger format relative to maintaining a significant degree of original interstitial volume between filler materials can also benefit from particle exposure. Due to the low content of polymer in the composition and the relatively high level of exposure of the filler material, the filler, if present, can act as pillars to maintain pore channels throughout the filled polymer matrix after compression.

[0034] The method for making the composition may include at least one of the following: being able to avoid the need for a substrate, faster manufacturing capability of the final composition, or reducing more than 90 wt% of the solvent and non-solvent used in the phase inversion process in the drying operation. In addition, unlike other processing techniques for forming highly filled compositions, the typical repulsive forces that exist between particles can be overcome. In the absence of special instructions, it is believed that small amounts of polymer can be used to consolidate high levels of fillers and bring the fillers into close proximity.

[0035] Unlike other typical phase inversion processes, the present method of mixing a solvent mixture with a non-solvent by introducing a bulk polymer film into a non-solvent bath under low shear mixing conditions enables the polymer chains to be highly entangled with each other to embed or attach filler particles. Compared with other phase inversion processes, such as those based on quenching in a non-solvent bath, solvent evaporation, or by thermal phase inversion, the present method can also reduce the shrinkage, contraction, or reeling of the polymer chains.

[0036] The present method may include forming a solvent mixture comprising a polymer, a solvent and an optional filler. The solvent mixture may be formed by mixing the polymer and the filler with a solvent to dissolve the polymer and form a solvent mixture. The solvent mixture may be formed by dissolving the polymer in a solvent and then adding the filler to form a solvent mixture. In the solvent mixture, the polymer may be completely dissolved in the solvent, and the added filler may be mixed to prepare a uniform solvent mixture. The solvent mixture may be formed by dissolving the polymer in a solvent, and the non-solvent may include the filler.

[0037] As readily determined by those skilled in the art, the solvent mixture may include a sufficient amount of solvent to dissolve the polymer. Forming the solvent mixture may include mixing for a sufficient amount of time to dissolve the polymer, which may range from a few minutes to a few hours depending on the intensity of the mixing and the relative amounts of solvent and polymer. The solvent mixture may be mixed until a slurry is formed in which the filler is suspended in the solvent mixture.

[0038] Based on the total weight of the mixture minus any solvent, the solvent mixture can include 0wt% to 98wt%, or 85wt% to 98wt%, or 90wt% to 96wt% filler. Based on the total weight of the mixture minus any solvent, the solvent mixture can include 2wt% to 100wt%, or 2wt% to 15wt%, or 4wt% to 10wt% polymer.

[0039] After forming the solvent mixture, the solvent mixture is combined with a non-solvent to form a precipitate containing fillers in a fibrillated polymer matrix. At least one of the solvent mixture or the non-solvent may contain fillers. Note that after combining with the non-solvent, the precipitate is not in the form of a layer, but can be considered as particles. The particles can have any size, but are separated from each other. In terms of the degree of particle contact, the particles are not firmly bound to each other and can be easily separated, for example, by filtering, stirring, etc. Note also that the term "non-solvent" is only used to indicate that the polymer matrix is ​​less soluble in the non-solvent compared to the solvent, and combining the solvent mixture with the non-solvent causes particle precipitation. The combination with the non-solvent causes a phase conversion of the polymer dissolved in the solvent to a precipitated polymer matrix present in the non-solvent, because the solvent diffuses out of the non-solvent.

[0040] Without intending to be bound by theory, it is believed that during the combination, the interfacial surface tension between the non-solvent and the filler material may cause repulsive forces between the filler and the non-solvent due to the difference in their relative surface energies. This difference is believed to cause a high level of exposure of the filler surface in the composition. For example, during phase inversion using water as a non-solvent, the hydrophobic carbon material in the acetone-polymer solution may preferably be deposited on the surface of the hydrophobic polymer. Therefore, the resulting composition comprises filler particles having pores that are highly exposed to the composition.

[0041] The combination can include injecting solvent mixture into non-solvent via injection nozzle during combination to cause shear on solvent mixture. The combination can include mixing during combination to cause shear on solvent mixture. Compared to continuous electrospinning composition and fibrillation polymer composition, the mixing and the phase transition material thus formed lead to the higher yield of polymer-filler structure. Applying shear can promote the fibrillation of polymer matrix. The combination of solvent mixture and non-solvent can occur when solvent mixture and non-solvent are actively mixed, for example, at least one of solvent mixture or non-solvent can be added only (for example, poured into or injected or otherwise) to another one of solvent mixture or non-solvent when not actively mixed (for example, without stirring with a stirring rod).

[0042] The solvent or non-solvent can each independently have a 15 MPa 1 / 2 (MPa) 1 / 2 ≤δ d ≤20MPa 1 / 2 or 16MPa 1 / 2 ≤δ d ≤18.5MPa 1 / 2 Delta d Hansen solubility parameter. A solvent may have a solubility of 5 MPa 1 / 2 ≤δ p ≤18MPa 1 / 2 or 8.5MPa 1 / 2 ≤δ p ≤16.5MPa 1 / 2 Delta p Hansen Solubility Parameter. A solvent or non-solvent can have a solubility of 4 MPa 1 / 2 ≤δ h ≤12MPa 1 / 2 or 5MPa 1 / 2 ≤δ h ≤11.5MPa 1 / 2 δ h Hansen solubility parameters. The solvent or non-solvent may include at least one of acetone, cyclohexanone, dimethylacetamide (DMAc), methyl ethyl ketone, N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), tetrahydrofuran (THF), tetramethylurea, or trimethyl phosphate.

[0043] As mentioned above, the non-solvent can be any solvent in which the polymer dissolving power is less than that of the solvent. The solvent or non-solvent can have a 12 MPa 1 / 2 ≤δ d ≤14.9MPa 1 / 2 Delta dHansen solubility parameter. Solvents and non-solvents can each independently have a solubility of 0 MPa 1 / 2 ≤ δ p ≤ 8 MPa 1 / 2 or 1MPa 1 / 2 ≤ δ p ≤ 4.9 MPa 1 / 2 δ p Hansen Solubility Parameter. A solvent or non-solvent can have a solubility of 13 MPa 1 / 2 ≤δ h ≤50MPa 1 / 2 or 15MPa 1 / 2 ≤δ h ≤45MPa 1 / 2 Delta h Hansen solubility parameters. The solvent or non-solvent may comprise at least one of an acid solution, an alcohol (e.g., C1-C12 alkanol), an aliphatic hydrocarbon, an aromatic hydrocarbon, an alkaline solution, butyrolactone, N-butyl acetate, carbitol acetate, diisobutyl ketone, dimethyl phthalate, ethyl acetoacetate, glycol ether, glycol ether ester, triacetin, a halogenated solvent, isophorone, methyl isobutyl ketone, propylene carbonate, triethyl phosphate, or water. The pH of the acid solution or alkaline solution is selected to not significantly degrade the polymer used in the composition. For example, the pH of the acid solution may be 1 to 6.5, while the pH of the alkaline solution may be 7.5 to 11.

[0044] The non-solvent may be present in excess of the solvent. For example, the volume ratio of the non-solvent to the solvent may be from 2:1 to 1000:1 or from 10:1 to 500:1.

[0045] Without intending to be bound by theory, it is believed that when forming a composition, if the polymer molecules can roll back or collapse back into a dense, coiled structure with little elongation, entanglement or interpenetration with other adjacent polymer molecules, the polymer may not be effective in bonding various fillers including active materials, and the structural integrity of the polymer may be insufficient. It has been found that it is desirable to form a composition or other membrane with a polymer that is more fully extended and entangled with both the particulate material (e.g., an inert filler or active battery electrode material) and with adjacent extended polymer chains. Without being bound by theory, it is believed that a single polymer chain - essentially deployed as a single "thread" extending and entangled with adjacent polymer chains and through a large amount of particulate material (powder, fiber, flake, agglomerate, etc.) - provides maximum capture (i.e., structural stability) to constrain the particles and keep the particles exposed and in close contact with each other (improving ion rate performance and electron rate performance, respectively).

[0046] Can tell (separate) precipitate from liquid phase (solvent and non-solvent) then.Separation can comprise relative precipitate to drain solvent and non-solvent, filter (by gravity or under reduced pressure) or centrifuge at least one.On the one hand, precipitate can for example be separated from liquid phase quickly with the speed that relative precipitate is removed the solvent and non-solvent that is greater than or equal to 95 weight percents or is greater than or equal to 99 weight percents in being less than or equal to 15 seconds or being less than or equal to 1 second.Therefore, this technology is suitable for large-scale or economical manufacturing.

[0047] The precipitate can be used as, for example, to separate with the liquid phase in the form of particles, or the separated precipitate can then be formed into a layer. The layer can be formed by depositing the precipitate on a substrate (e.g., a flat substrate) and drying the precipitate to remove any residual solvent and non-solvent. Forming the layer can include at least one of thermoforming, calendering, lamination, roller coating or other methods. Multilayers can be formed by depositing the precipitate in sequence and molding multiple layers at one time or by molding after each deposition.

[0048] The separated precipitate can be used to make other shapes, such as fibers or other three-dimensional shapes. It can be formed by extrusion, pasting, trawling, thermoforming, calendaring, lamination, roller coating, molding or other methods of forming shapes.

[0049] The benefit about the present composition can be derived from the optimized structure, including molecular structure, micro / nano structure and macrostructure. Considering the molecular structure, filler and polymer can be selected based on the desired purpose. Filler can include salt, metal oxide, silicon dioxide (for example, hydrophobic fumed silica or hydrophilic fumed silica), glass, silica glass such as glass fiber or other types of glass, carbonaceous material (for example, carbon black, carbon fiber, carbon nanofiber, graphite or graphene), organic material (for example, polymer in the form of powder insoluble in solvent, such as ethyl cellulose), non-metallic oxide, clay, quartz, calcium carbonate or other specific organic materials such as particle rubber (for example, styrene-based copolymer, such as acrylonitrile-butadiene-styrene) or wood pulp at least one. Filler can include at least one of titanium dioxide, silicon dioxide, boron nitride, activated carbon or carbon black. Filler can be in the form of at least one of particles (for example, spherical or irregular shape), agglomerates, flakes, fibers or whiskers. At least one of non-solvent mixture or solvent includes filler. The filler can be a soluble filler. For example, the non-solvent can include the first filler, and the solvent can include the second filler. If the polymer includes a fluoropolymer or an epoxy resin, the filler can include at least one of clay, quartz, calcium carbonate or wood pulp. The filler can include a soluble filler. The soluble filler can include a salt (e.g., sodium chloride, ammonium chloride, sodium sulfate or calcium chloride). If the filler includes a soluble filler, after the soluble filler dissolves, the composition can include 0wt% to 15wt% or 0wt% to 1wt% or 0wt% of the soluble filler based on the composition minus the resulting total weight of any solvent.

[0050] The filler may have an average maximum particle size less than or equal to 50 microns, or less than or equal to 5 microns, which may be determined by dynamic light scattering.The filler may include a multimodal particle distribution, for example to increase the packing of the filler in the composition.

[0051] The polymer may include at least one of a fluoropolymer (e.g., polyvinylidene fluoride (PVDF)), an acrylic polymer, a polyolefin, a polyacrylonitrile, a nylon, a polyester, a polyamide, a polyether, a rubber, a poly(vinyl chloride), a poly(vinyl acetate), a poly(vinyl alcohol), a poly(vinyl pyrrolidone), or a silane. If the polymer includes a hydrophobic polymer (e.g., a fluoropolymer), the solvent may include a hydrophobic solvent such as acetone, and the non-solvent may include a hydrophilic non-solvent such as water. If the polymer includes a hydrophilic polymer (e.g., poly(vinyl alcohol)), the solvent may include a protic solvent or a polar solvent such as water, and the non-solvent may include a non-polar non-solvent such as acetone.

[0052] Table 1 shows a non-limiting overview of various materials that may be used in the present disclosure.

[0053]

[0054] The micro / nanostructure of the polymer can include elongated polymer chains or fibrils that can entangle with adjacent elongated chains to form a compact matrix around the filler to maintain the shape of the composition, so the resulting composition can have improved properties. The end result of having a high level of polymer molecular elongation within the bulk polymer body can include a composition with improvements in at least one of strength, elongation at break, modulus, or thermal response compared to a composition comprising the same material but formed by a different process.

[0055] Considering the macroscopic structure of the composition, the composition may be in the form of at least one of particles, beads, filaments, fibers, or agglomerates, or the composition may be in the form of a layer.

[0056] The void content (porosity) of the composition can be from almost solid to extremely porous. According to the medium provided with the composition, the composition can be impermeable to extremely porous and permeable. The composition can have a porosity of up to 90 volume percent equal to the tap density of the filler and based on the gross volume of the composition. The composition can have a combination of macropores (having an average pore size greater than 50 microns), mesopores (having an average pore size of 2 microns to 50 microns) and micropores (having an average pore size less than 2 nanometers). Compositions can be compressed to reduce porosity, for example, by calendering. Based on the gross volume of the composition, the porosity after the reduction can be 35 volume percent to 50 volume percent.

[0057] The ability to indicate macrostructure can be achieved by controlling factors related to the starting formulation or process variables before or during the composition is formed. For example, an initial solution with a high solvent, high filler and low polymer ratio for producing a composition in the form of particles or filaments can be post-processed, such as casting to form a layer. Other factors include adjusting the ratio of filler to polymer and the mixing dynamics and the amount of shear applied (for example, by controlling the mixing time, mixing speed or the ratio of solvent to non-solvent). The control of such a configuration of the composition can enable optimization for various purposes.

[0058] The ability to produce compositions with different macrostructures can enable them to be used in a large number of different applications. For example, particles can work well in fluidized bed reactors or when deposited on or inside cloth, filters or other fiber products. When high-porosity membranes are used, thin-walled membranes can, for example, be used as battery components such as battery separators or as filter membranes. When less porous or even solid membranes are arranged in a pleated structure in a chamber, the composition can be used as a high surface area medium through which solutions for bioreactors can pass. Thick block structures can have multiple uses, such as absorbent materials or high-throughput filters that can capture large amounts of particles of interest.

[0059] The uniqueness of the present disclosure is that, only by changing the formula or process control, the different macrostructures of the composition can be optimized accordingly for the article. The ability to easily adjust the final properties of the composition only by modifying the process is contrary to the conventional method. For example, the use of solvent coating technology is generally used for film production, but sintering is usually required to produce bulk structures such as blocks or rods. The present method can be considered to be based on the formation of a thick slurry or paste (paste of particles) with a large amount of solidified polymers suspended in a liquid phase (including solvents and non-solvents) and with a filler mixed and attached to each other, which can then be coated, sprayed, pressed, molded, cast or otherwise formed into a final shape, which can be changed across a wide range of dimensional parameters, from thin or narrow to wide and large with an aspect ratio of almost any length and short size, including a curled shape and an irregular shape.

[0060] One particularly advantageous processing technique for producing sheets or films involves using the liquid dispersion / slurry of the composition produced by the phase inversion process in a typical papermaking process. Use of a FOURDRINIER or HATSCHEK machine or other wire screen dewatering system can enable the production of paper or nonwoven films, which can then be further pressed, bonded together, or otherwise manufactured in the same manner as any typical fiber mat preparation process.

[0061] Based on the total weight of the composition, the composition may include 0 wt% to 99 wt%, or 85 wt% to 99 wt%, or 90 wt% to 98 wt%, or 90 wt% to 96 wt% of filler. Based on the total weight of the composition, the composition may include 1 wt% to 100 wt%, 1 wt% to 15 wt%, or 2 wt% to 10 wt%, or 4 wt% to 10 wt% of polymer matrix. The weight ratio of filler to polymer may be greater than or equal to 8:1 or 9:1 to 50:1.

[0062] A layer can be formed from the composition. The layer can have a thickness of 0.01 to 100 millimeters, or 0.1 to 50 millimeters, or 1 to 10 millimeters, or 0.05 to 10 millimeters. The layer can have a thickness that can make it self-supporting, wherein the layer does not need to be supported by the base layer to maintain its structural integrity. This feature can make the handling and processing of the composition easier.

[0063] The composition can be in the form of a layer (which includes a film, a sheet, etc.), a plurality of fibers, a molding, or a film. The composition can be used in an electrode of a battery. The composition can be used in an electrode for an electrochemical cell. A typical electrochemical cell, whether aqueous or non-aqueous, primary or secondary, or other various battery types, will typically have one or more particulate materials (called active materials) that react with various electrochemical substances such as hydrogen protons or hydroxide substances, anionic or cationic molecules, water or hydration products, etc. One of the purposes of using polymers to produce these electrodes is to form a stable physical structure (electrode) that can almost completely expose the active material to the ionic substance via its electrolyte medium.

[0064] In a particular example, the composition can be used as a separator in a battery, wherein the polymer can include poly(vinylidene fluoride), the filler can include at least one of hydrophobic fumed silica, hydrophilic fumed silica, glass fiber, particulate thermoset, and the non-solvent can include a solution of at least one of poly(vinyl alcohol), ethyl cellulose, hydrophobic fumed silica, or hydrophilic fumed silica in at least one of water or alcohol. The composition can be used in the cathode of a battery, wherein the polymer includes poly(vinylidene fluoride), the filler includes lead dioxide, and the non-solvent includes at least one of water or alcohol and an optional metal (e.g., titanium or germanium). The composition can be used as a high-power capacitor (e.g., for wireless charging), wherein the polymer can include at least one of poly(vinylidene fluoride) or poly(amide-imide), and the filler can include at least one of a salt or boron nitride.

[0065] In summary, the present method can produce a composition with improved properties by converting the polymer from a dissolved material to a precipitated material while preventing the chain from winding back or agglomerating into spherical molecules due to the presence of the filler. The composition can be used in an article, for example, in a filter, an adsorption membrane, a battery, an electrochemical cell, or a reactor (e.g., a fluidized bed or a bioreactor).

[0066] The following examples are provided to illustrate the present disclosure. The examples are illustrative only and are not intended to limit devices prepared according to the present disclosure to the materials, conditions, or processing parameters set forth therein.

[0067] Example

[0068] Example 1: Preparation of anode using phase inversion technique

[0069] Porous carbon black-PVDF anode (C-PVDF) was prepared using water as a non-solvent using phase inversion technology. 1 gram of PVDF was dissolved in 42.5 grams of acetone. 19 grams of carbon black was added to the PVDF mixture and mixed to form a solvent mixture at 10 revolutions per minute via a SILVERSON mixer. Part of the solvent mixture was injected into 25 milliliters of water and the precipitate was filtered until all solvent mixtures were precipitated by quickly spraying the solvent mixture into water via a pipette. Water was actively mixed via a stirring rod during injection. PVDF fibrillated in the presence of carbon black and formed a composition. Filtering was performed by pouring on a coffee filter. The precipitate was dried at 90 degrees Celsius (°C) to remove acetone and water, and the precipitate was compressed to form a self-supporting pad with a thickness of 2 millimeters. The pad was then dried again at 130°C.

[0070] Figure 1 is a photographic image of a carbon-PVDF layer having a thickness of 2 mm. Figure 2 , Figure 3A and Figure 3B are scanning electron microscope images of the carbon-PVDF layer at different magnifications. Figure 3B The presence of a fibrillated network with a high degree of exposed filler surface area is clearly shown.

[0071] Example 2: Comparative Polymer Films

[0072] According to US Pat. No. 8,147,732, unfilled polymer membranes and filled polymer membranes were prepared by different phase inversion processes. Scanning electron microscope images were taken and Figure 4 and Figure 5 Shown in. Figure 4 The formation of a porous material is shown. Figure 5 It is shown that the filler is completely covered by the polymer, in other words, there is no surface area where the filler is exposed.

[0073] Example 3: Comparison of the phase inversion method of Example 1 with different methods

[0074] A photograph of a composition having a precipitate present in the solvent and non-solvent after phase inversion of Example 1 was taken, wherein the weight ratio of filler to PVDF was 95:5 and the weight ratio of water to acetone was 90:10. Fig.6A1 and Fig.6A2 A top view and a side view are shown in FIG. Fig.6A1 It is shown that there is no filler present on the edge of the dish or on the surface of the solution. Fig.6A2The filler is shown to be located in the precipitate, as indicated by the transparent layer of solvent / non-solvent in the middle of the dish. These two figures show that the carbon filler is actually bound to the PVDF polymer.

[0075] The same materials were used but different processes were used to form a phase inversion solution. Fig.6B1 and Figure 6B2 A top view and a side view are shown in FIG. Fig.6B1 The carbon filler is shown to be located at the edge of the dish and on the surface of the solution. Figure 6B2 The filler is shown to be dispersed throughout the solution. These two figures indicate that the carbon filler is not bound to the PVDF polymer.

[0076] Example 4: Formation of PVDF Composition

[0077] 1 gram of PVDF is dissolved in 42.5 grams of acetone, and 19 grams of sodium chloride is added to form a solvent mixture by mixing at ambient temperature (about 23°C). Part of the solvent mixture is injected into 25 milliliters of water by quickly spraying the solvent mixture into the water via a pipette and the precipitate is filtered until all the solvent mixture is precipitated. PVDF fibrillates in the presence of salt crystals and forms a composition. Filtering is performed by pouring on a coffee filter. The salt is washed out to obtain a fibrillated PVDF without salt. The fibrillated PVDF is dried at 90°C to remove acetone and water, and the fibrillated PVDF is compressed to form a self-supporting pad. The pad is then dried again at 130°C. The same treatment is performed in the absence of salt, and PVDF is precipitated from the solution without forming fibrils.

[0078] Fig. 7A is a scanning electron microscope image of PVDF after salt removal. Elemental analysis of PVDF after salt removal was performed and the results are in Figure 7B and Figure 7C Shown in.

[0079] Example 5: Formation of Poly(vinyl alcohol) Compositions

[0080] A poly(vinyl alcohol) composition was prepared according to Example 1, except that 0.5 grams of poly(vinyl alcohol) was dissolved in 20 grams of water; 4.25 grams of titanium dioxide and 0.25 grams of silicon dioxide were added as fillers; and the solvent composition was added to 3 grams of acetone as a non-solvent. A phase inversion composition was formed.

[0081] Example 6: Formation of PVDF-HFP Composition

[0082] A PVDF-HPF composition was prepared according to Example 1, except that 0.25 grams of poly(vinyl alcohol-hexafluoropropylene) was dissolved in 20 grams of acetone; 4.75 grams of carbon black was added as a filler; and the solvent composition was added to 3 grams of isopropanol as a non-solvent. The process was repeated, varying the weight ratio of polymer to carbon black from 0.25 grams:4.75 grams to 0.5 grams:4.5 grams and 0.75 grams:4.25 grams. A phase inversion composition was formed.

[0083] Example 7: Formation of Polystyrene Compositions

[0084] A polystyrene composition was prepared according to Example 1, except that 0.5 grams of polystyrene was dissolved in 20 grams of xylene; 5 grams of activated carbon was added as a filler; and the solvent composition was added to 3 grams of water as a non-solvent. A phase inversion composition was formed.

[0085] Example 8: Formation of Poly(amide-imide) Compositions

[0086] A poly(amide-imide) composition was prepared according to Example 1, except that 0.75 g of poly(amide-imide) was dissolved in 20 g of DMAC; 5 g of hexagonal boron nitride was added as a filler; and the solvent composition was added to 3 g of ethylene glycol as a non-solvent. A phase inversion composition was formed.

[0087] Non-limiting aspects of the disclosure are set forth below.

[0088] Aspect 1: A method for preparing a composition, the method comprising: forming a solvent mixture comprising a polymer and a solvent; precipitating the solvent mixture using a non-solvent to form the composition comprising a filler in a fibrillated polymer matrix, wherein the composition is in the form of particles and at least one of the solvent and the non-solvent comprises a filler; and separating the composition relative to the solvent and the non-solvent to separate the composition.

[0089] Aspect 2: A method according to Aspect 1, wherein the composition comprises: greater than or equal to 75 weight percent of the filler; and 1 weight percent to 25 weight percent of the fibrillated polymer matrix; wherein the above weights are based on the total weight of the composition minus any solvent; or wherein based on the total weight of the solvent mixture, the solvent mixture comprises greater than or equal to 50 weight percent to 95 weight percent of the solvent.

[0090] Aspect 3: The method according to any one or more of the preceding aspects, wherein at least one of the solvent and the non-solvent comprises at least one of acetone, cyclohexanone, dimethylacetamide, methyl ethyl ketone, N,N-dimethylformamide, dimethyl sulfoxide N-methylpyrrolidone, tetrahydrofuran, tetramethyl urea, or trimethyl phosphate; and wherein the other of the solvent and the non-solvent comprises at least one of an acid solution, an alcohol, an aliphatic hydrocarbon, an aromatic hydrocarbon, an alkaline solution, butyrolactone, N-butyl acetate, carbitol acetate, diisobutyl ketone, dimethyl phthalate, ethyl acetoacetate, ethylene glycol ether, ethylene glycol ether ester, triacetin, a halogenated solvent, isophorone, methyl isobutyl ketone, propylene carbonate, triethyl phosphate, or water.

[0091] Aspect 4: The method according to any one or more of the preceding aspects, wherein combining the solvent mixture with the non-solvent comprises pouring or injecting the solvent mixture into the non-solvent; and wherein the combining comprises active mixing.

[0092] Aspect 5: A method according to any one or more of the preceding aspects, wherein separating the precipitate comprises at least one of draining, sieving or filtering the precipitate, preferably at a rate of removing greater than or equal to 95 weight percent or greater than or equal to 99 weight percent of the solvent and the non-solvent relative to the precipitate in less than or equal to 15 seconds or less than or equal to 1 second; and drying the composition.

[0093] Aspect 6: The method according to any one or more of the preceding aspects, further comprising forming a layer, optionally wherein multiple layers form the composition, wherein forming the composition comprises extruding, pasting, molding, trawl, thermoforming, calendaring, laminating, roller coating or other methods of forming a layer.

[0094] Aspect 7: A method according to any one or more of the preceding aspects, wherein the filler comprises at least one of salt, metal oxide, silica, glass, silica glass, carbonaceous material, organic material, non-metallic oxide, clay, quartz, calcium carbonate, granular rubber, glass fiber or wood pulp.

[0095] Aspect 8: A method according to any one or more of the preceding aspects, wherein the filler comprises a soluble filler, and wherein the method further comprises dissolving the soluble filler from the composition, wherein the composition contains 0 wt% to 15 wt%, or 0 wt% to 1 wt% of the soluble filler based on the total weight of the composition minus any solvent.

[0096] Aspect 9: The method according to any one or more of the preceding aspects, further comprising forming a layer from the composition, wherein forming the layer comprises at least one of thermoforming, calendering, laminating, or roll coating the composition.

[0097] Aspect 10: A method according to any one or more of the preceding aspects, wherein the polymer comprises at least one of a fluoropolymer, an acrylic polymer, a polyolefin, a polyacrylonitrile, a nylon, a polyester, a polyamide, a polyether, a rubber, a poly(vinyl chloride), a poly(vinyl acetate), a poly(vinyl alcohol), a poly(vinyl pyrrolidone), a silane, or an epoxy resin.

[0098] Aspect 11: A composition formed by the method described in any one or more of the preceding aspects.

[0099] Aspect 12: A composition according to the previous aspect, wherein the composition has at least one of a porosity equal to or higher than the tap density of the filler, the composition is in the form of a layer having a thickness of 0.05 mm to 10 mm, or 2.5 mm to 5 mm, or wherein the composition is in a self-supporting form.

[0100] Aspect 13: An article comprising the composition according to aspect 11 or 12, wherein the article is a filter, an insulator, a capacitor, an electrode, a battery, or a separator.

[0101] Aspect 14: A porous material manufactured by the method of any one or more of Aspects 1 to 10, wherein after removing the solvent and the non-solvent, the filler particles are mechanically bonded together by the polymer, and wherein the polymer exists as filaments that adhere to the filler particles and connect the filler particles through the interstitial spaces between the filler particles; and wherein each filler particle has a filament connection with one or more other particles.

[0102] Aspect 15: A porous material according to Aspect 14, wherein the filaments are arranged in the interstitial spaces between the filler particles so that the packing density of the filler does not change compared to filler particles not containing the polymer, and so that the void volume of the porous material does not change substantially relative to particles not containing the filler, except that it is proportional to the volume of the voids replaced by the polymer.

[0103] Aspect 16: The porous material according to Aspect 14 or 15 has: a void content of 40 volume percent to 99 volume percent, or 50 volume percent to 95 volume percent; wherein the average filler particle size is micron or submicron, and the polymer filaments have an average diameter less than or equal to 0.5 microns and a length less than or equal to 2 microns; or the average filler particle size is less than or equal to 100 microns, or less than or equal to 10 microns, and the polymer filaments have an average diameter of 5% to 50% of the filler diameter; and wherein the nominal filament length connecting adjacent particles is 1% to 500% of the average filler diameter.

[0104] Aspect 17: A porous material according to any one or more of Aspects 14, 15 or 16, wherein both the filler and the polymer are arranged in a uniform distribution without agglomeration or clumping of the filler or coagulation or stratification of the polymer, and wherein the surface area of ​​the filler exposed to the pores is greater than or equal to 50 area percent, or greater than or equal to 95 area percent.

[0105] Aspect 18: A porous material according to any one or more of Aspects 14, 15, 16 or 17, wherein the porous material has a uniform porosity throughout the porous material and has a pore symmetry with a bubble point less than 10 times and preferably less than 2 times the minimum pore diameter.

[0106] Aspect 19: A porous material precipitated from a polymer solution produced by phase inversion, wherein a majority of the liquid, including solvent and non-solvent, typically 90% or more, is mechanically removed (e.g., by at least one of filtration, sedimentation, decantation, centrifugation, spraying, or cake compression). Mechanical removal can be more economical and faster than that achieved by typical phase inversion processes that rely on drying, evaporation, liquid bath quenching, liquid extraction, or the like to remove liquid from the porous material.

[0107] Aspect 20: A solution according to Aspect 19, wherein the porous structure having a polymer-filler structure produced after the initial liquid removal is used as a precursor for producing products by conventional pulp processing equipment (e.g., paper machines, filter presses, etc.), the porous material being stabilized to maintain the porous structure of interspersed polymers and fillers while the liquid fills all or some of the pores, wherein the liquid content is further reduced by at least one of drying, evaporation, compression, etc. to produce a cohesive mass of porous material that does not contain liquid.

[0108] Compositions, methods and articles may alternatively include, consist of, or consist essentially of any suitable material, step or component disclosed herein. Compositions, methods and articles may additionally or alternatively be formulated to be free of or essentially free of any material (or substance), step or component that is not necessary to achieve the function or purpose of the composition, method and article.

[0109] The terms "a" and "an" do not represent a limitation of quantity, but rather represent the presence of at least one of the referenced items. Unless the context clearly indicates otherwise, the term "or" means "and / or". References to "aspects", "embodiments", "another embodiment", "some embodiments", etc. throughout the specification mean that specific elements (e.g., features, structures, steps, or characteristics) described in relation to the embodiment are included in at least one embodiment described herein, and may or may not be present in other embodiments. In addition, it should be understood that the described elements may be combined in any suitable manner in various embodiments.

[0110] When an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements.

[0111] Unless indicated to the contrary herein, all test standards are the latest standards in effect on the filing date of this application or, if priority is claimed, on the filing date of the earliest priority application in which the test standards appear.

[0112] The endpoints of all ranges involving the same component or characteristic include the endpoint, can be independently combined, and include all intermediate points and ranges. For example, the range of "up to 25wt% or 5wt% to 20wt%" includes the endpoints and all intermediate values ​​of the range of "5wt% to 25wt%, such as 10wt% to 23wt% etc.

[0113] The term "a combination comprising at least one of the foregoing" or "at least one" is meant to include each element of the list individually, as well as combinations of two or more elements of the list, and combinations of at least one element of the list with unnamed similar elements. Additionally, the term "combination" includes blends, mixtures, alloys, reaction products, and the like.

[0114] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.

[0115] All cited patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term in the present application contradicts or conflicts with a term in the incorporated reference, the term in the present application takes precedence over the conflicting term in the incorporated reference.

[0116] Although specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are not currently foreseeable or may not be foreseeable may occur to applicants or other persons skilled in the art. Therefore, the appended claims as filed and as they may be amended are intended to cover all such alternatives, modifications, variations, improvements, and substantial equivalents.

Claims

1. A method for preparing a composition, the method comprising: forming a solvent mixture comprising a polymer and a solvent; combining the solvent mixture with a non-solvent to precipitate a composition comprising a plurality of filler particles in a fibrillated polymer matrix, wherein the composition is in the form of particles, wherein the filler particles are mechanically bonded to at least one or more filler particles by one or more polymer fibers passing through interstitial spaces within the formed particles, and wherein the polymer fibers are deposited in an elongated form within the interstitial spaces between the filler particles, the filler particles having bonded filamentary connections to at least one other particle, wherein prior to precipitation, at least one of the solvent and the non-solvent contains the filler particles; After precipitating the composition, removing greater than or equal to 95 percent of the solvent and the non-solvent from the composition; and Reducing the volume of interstitial spaces between dispersed filler particles, so that the interstitial spaces present within a plurality of uniformly dispersed filler particles are reduced; wherein the composition is porous and has a void content, less any liquid, of from 40 volume percent to 99 volume percent and a filler content greater than or equal to 90 volume percent, based on the total volume of the composition, wherein the filler particles are attached to the polymer or embedded within the composition, and wherein the surface area of ​​the filler exposed to the pores is greater than or equal to 50 area percent; Wherein, based on the total weight of the composition minus any liquid, the composition comprises: greater than or equal to 90 weight percent of the filler and 1 weight percent to 10 weight percent of the fibrillated polymer matrix; wherein the average filler particle size is less than or equal to 100 microns, and the polymer filaments have an average diameter of 5% to 50% of the filler diameter.

2. The method of claim 1, wherein separating the composition comprises: At least one of draining, sieving or filtering the precipitate in less than or equal to 15 seconds; as well as The composition is dried.

3. The method according to claim 1, wherein the composition has at least one of a porosity equal to or higher than the tap density of the filler, the composition is in the form of a layer having a thickness of 0.05 mm to 10 mm, or wherein the composition is in a self-supporting form.

4. The method of claim 1, wherein the filler is in the form of at least one particle selected from the group consisting of spherical shapes, irregular shapes, agglomerates, flakes, fibers, whiskers, and multimodal particle distribution.

5. The method according to claim 1, wherein the function of the filler comprises at least one of catalysis / enzyme action, filtration / binding properties, direct chemical reaction and biological purification.

6. The method according to claim 1, wherein the induced precipitation filaments are drawn into shapes such as cylindrical, flat ribbon, hollow and spiral by using fillers and mixing conditions, enabling the production of polymer fibers of various morphologies.

7. The method of claim 1, wherein the composition is used as a reinforcing and functional additive in a material selected from the group consisting of concrete, gypsum, hydraulic cement, thermosetting polymer resins, thermoplastics, paper, nonwoven fabrics, solid films, and porous films.

8. The method of claim 1, wherein the composition is used as an additive in an article selected from the group consisting of cellulose pulp, glass fibers, ceramic fibers, and metal fibers.

9. The method of claim 1, wherein the deposition of filaments extends to the surfaces of a plurality of particles, and a plurality of branches of the filaments form a mesh-like fiber network.

10. The method of claim 1, wherein the composition is used in an application selected from the group consisting of liquid filtration, gas filtration, thermal insulation, and building materials.

11. The method of claim 1, wherein the composition in the form of dry particles is used for impregnation with a binder.

12. The method of claim 1, wherein the composition is made by using auxiliary additives in a solvent mixture or a non-solvent bath to be deposited into the pulp material and retained in the pulp material.

13. The method of claim 1, wherein the composition is used to make an article selected from the group consisting of paper, nonwoven fabrics, inorganic substances, polymers, and molded articles.

14. The method of claim 1, wherein the composition is used in articles requiring high filler content, wherein the polymer fibers act as a binder material to help secure the filler.

15. The method of claim 1, wherein combining the solvent mixture with the non-solvent comprises pouring or injecting the solvent mixture into the non-solvent.

16. The method of claim 1, further comprising forming a layer, optionally wherein a plurality of layers form the composition, wherein forming the composition comprises extruding, pasting, molding, trawl, thermoforming, calendaring, laminating, or roll coating.

17. A porous material manufactured by the method of claim 1, wherein the porous material is made non-porous by a post-processing step of applying compression and / or heating, and wherein the filaments are arranged in the interstitial spaces between the filler particles so that the packing density of the filler is unchanged compared to filler particles not containing the polymer, and so that the void volume of the porous material is substantially unchanged relative to particles not containing the filler, except in proportion to the volume of the voids replaced by the polymer.

18. The porous material according to claim 17, wherein both the filler and the polymer are arranged in a uniform distribution without agglomeration or lumps of filler or coagulation or stratification of polymer, and The surface area of ​​the filler exposed to the pores is greater than or equal to 50 area percent.

19. A porous material comprising: A composition comprising a plurality of fillers in a fibrillated polymer matrix; 40 volume percent to 99 volume percent void content; wherein the average filler particle size is micron or submicron, and the polymer filaments have an average diameter less than or equal to 0.5 microns and a length less than or equal to 2 microns; or The average filler particle size is less than or equal to 100 microns, or less than or equal to 10 microns, and the polymer filaments have an average diameter of 5% to 50% of the filler diameter; and The nominal filament length connecting adjacent particles is from 1% to 500% of the average filler diameter.

20. The porous material according to claim 19, wherein both the filler and the polymer are arranged in a uniform distribution without agglomeration or lumps of filler or coagulation or stratification of polymer, and The surface area of ​​the filler exposed to the pores is greater than or equal to 50 area percent.

21. The porous material of claim 19, wherein the porous material has a uniform porosity throughout the porous material and a pore symmetry with a bubble point less than 10 times and preferably less than 2 times the smallest pore diameter.

22. A porous material precipitated from a polymer solution produced by phase inversion, wherein a substantial portion of the liquid, including solvent and non-solvent, typically 90% or more, is mechanically removed, such as by at least one of filtration, sedimentation, decantation, centrifugation, spraying or cake compression, in a manner that is generally more economical and faster than that achieved by typical phase inversion processes that rely on drying, evaporation, liquid bath quenching, liquid extraction or the like to remove liquid from the porous material.

23. A porous material according to claim 22, wherein the porous material having a polymer-filler structure produced after initial liquid removal is used as a precursor for producing articles by conventional pulp processing equipment such as a paper machine, filter press or similar equipment, the porous material is stabilized to maintain a porous structure of interspersed polymers and fillers while the liquid fills all or some of the pores, wherein the liquid content is further reduced by at least one of drying, evaporation or compression to produce a cohesive mass of porous material that does not contain liquid.

Citation Information

Patent Citations

  • Highly microporous polymers and methods for producing and using the same

    US8147732B2